An invitation to feminist ethics - Lindemann, Hilde (Oxford University Press, 2019)
Feminist ethics addresses how power, through gender, affects moral practice and theory. This enterprise is more important than ever before in an age of sharpened attention and concern for feminist issues and injustices. Yet the number of terms which have entered mainstream discussion can quickly overwhelm the novice: intersectionality, gender neutrality, androcentrism. An Invitation to Feminist Ethics offers an easy-to-understand, hospitable approach to the study of feminist moral theory and practice from a renowned ethicist, underscoring its need and the clarifying light it casts on some of the most pressing topics in contemporary society.The work surveys feminist ethical theory, beginning with an explanation of ethics, feminism, and gender before discussing the concepts of discrimination, oppression, gender neutrality, and androcentrism. The work further discusses in-depth intersectionality and microagressions before examining personal identities and how identities are vulnerable to oppression, and what can be done about it.The book also includes a helpful overview of three standard moral theories--social contract theory, utilitarianism, and Kantian ethics--and a discussion of their failings from a feminist point of view, followed by introductions to feminist care theory and feminist responsibility ethics. A "close-ups" section explores three social practices--bioethics, violence, and the globalized economy--within which these concepts are applied, and the need for feminist ethics is most urgent.